Comprehensive multispectral and computational study of isoxazolidine derivative ‘ISoXD3’: Synthesis, spectral characteristics, DNA binding, and comparative effects of allyl and propargyl groups on optical properties - Ibrahim A. Alhagri; Siwar Ghannay; Norah A. Al-Suwailem; Rania Hussien Al-Ashwal; Sadeq M. AlHazmy; Sabri Messaoudi; Kaiss Aouadi (Results in Chemistry)
In this article, we have synthesized and examined the spectral properties of the isoxazolidine derivative ISoXD3, particularly its UV–Visible and fluorescence spectra. ISoXD3 shows a strong absorbance peak at 228 nm (S₀ → S₂ transition) and another at 290 nm (S₀ → S₁ transition). The absorption spectra are stable in n-hexane and methanol but shift bathochromically in water due to hydrogen bonding. A notable Stokes shift of about 129 nm is observed in ethanol, indicating vibrational relaxation. The emission spectrum exhibits a 34 nm red shift related to the solvatochromic effect, highlighting solvent interactions. Increased solvent polarity decreases fluorescence intensity and quantum yield, suggesting significant solvation effects. Additionally, substituting the propargyl group with an allyl group in ISoXD3 in ethanol decreases excited-state stabilization but increases fluorescence intensity due to reduced steric hindrance and enhanced electronic transitions. Transitions were studied using DFT. This study investigates the interaction between the synthesized compound ISoXD3 and DNA using UV–Vis and fluorescence spectra. The UV–Vis spectral analysis revealed a red shift and hyperchromic effect, suggesting intercalative binding between ISoXD3 and DNA. EB displacement experiments further supported the intercalation hypothesis, showing a 50.6 % reduction in EB-DNA fluorescence. Docking studies have shown a favorable interaction of the molecule with DNA. Quenching analysis revealed static quenching behavior with a Stern-Volmer constant Ksv = 4.91 × 103 M−1, a quenching rate constant kq = 2.45 × 1011 M−1 s−1 and binding constant Kb = 1.44 × 104 M.